The Power of Inquiry-Based Chemical Change Lesson in Under-Resourced Classrooms: Perspectives of Grade 10 Learners - Nkosi, Nkosinathi Willy; Motlhabane, Abraham (Scientia in educatione, 2024)
This qualitative study delves into the learner experience of inquiry-based lessons, uncovering the perceptions and insights of learners engaged in this pedagogical approach. Through focus group interviews, we gathered rich data that reveals a transformative learning environment characterized by active engagement, collaborative discourse, and autonomy. Learners embraced the opportunity to explore concepts independently, seeking clarification from peers and cultivating a deeper understanding of the subject matter. Notably, despite feeling unsupported by their teachers, learners perceived the limited teacher involvement as a liberating force, fostering independence and encouraging more extensive reading and peer discussion. Our findings resonate with existing research, underscoring the efficacy of inquiry-based learning in promoting learner-centeredness, critical thinking, and conceptual understanding. The study's outcomes have significant implications for science education, highlighting the need for a paradigmatic shift from traditional teacher-centric approaches to learner-centered inquiry-based methods that empower students to take ownership of their learning.